Agama Masyarakat Keturunan Arab - Imam Subchi (Buletin Al-Turas, 2006)
The Arab heredity communities in Indonesia are immigrants from Hadramaut Yemen). Some of them have a status of sayid because they have a lost lineage to the prophet Muhammad saw. The sayid group has established an organization and school Jami'at Khair, while the non-sayid group established Al-Irsyad